First Japanese Garden in the Heart of Asia: A place where East meets West - Kuzevanov, Victor; Matsushima, Hajime; Yamada, Takuhiro; Sizykh, Svetlana; Ponomarev, Alexey (project baikal, 2015)
This article, through words and pictures, tells the story of how and why a small piece of Japanese cultural heritage – a genuine Japanese garden – was established in the heart of Asia in Irkutsk through a partnership between two sister-universities and a long lasting friendship between Russo-Japanese communities in both countries. The first Japanese garden was created in the greenhouse of the Botanic Garden of Irkutsk State University in 2012 to provide a new cross-disciplinary ethnobotanical and cultural facility for students and the local public. The 35-sq.m garden (7m x 5 m) was developed to provide an opportunity for visitors to experience one of the great horticultural art forms of the world without leaving Irkutsk.